A influência da obra de Vasco Vieira da Costa na afirmação da Arquitetura Moderna em Angola - Vumbi, Júlio Pemba (2024)
This dissertation has the peculiarity of showing the participation of Vasco Vieira da Costa (1911-1982) in the process of building an identity and modernist architecture in Angola, specifically in the capital city of Luanda, in the projection of several urbanization projects, as well as his trajectory as author of the first work considered at the time as a living element in the emergence of the modern movement in Angola. It is necessary to highlight that the end of the Second World War will mark the period in which industries will introduce a new literature on the use of materials and their way of producing and exploring, favoring the birth of new ideas and the use of aesthetic materials in construction. Through exploratory studies carried out throughout the research, we also sought to understand that the architect Vieira da Costa played a leading role in contributing to the emergence of the first architecture course in Angola. The emergence of this branch allowed a distinction between Civil Engineer and Architect, since in the past they were both considered Civil Engineer